Senegal : Agricultural Sector Risk Assessment - DAlessandro, Stephen (World Bank, Washington, DC, 2015)
The performance of Senegal’s agricultural performance exemplifies the impact of unmanaged risk on productivity among vulnerable smallholder crop producers and pastoralists. The government of Senegal has historically responded to drought and other shocks with direct financial support to farmers as well as general assistance to the rural population. The World Bank, with support from the group of eight (G-8) and the United States Agency for International Development (USAID) and in collaboration with the Ministry of Agriculture and Rural Equipment (MARE), commissioned the present study. The objective of this assessment was to assist the government of Senegal to: (1) identify, analyze, quantify, and prioritize principal risks facing the agricultural sector; (2) analyze the impact of these risks; and (3) identify and prioritize appropriate risk management interventions that may contribute to improved stability, reduced vulnerability, and increased resilience of agricultural supply chains in Senegal. This report presents a summary of the assessment’s key findings. Chapter one gives introduction. Chapter two provides an overview of the agricultural sector in Senegal and a discussion of key growth constraints. An assessment of the main agricultural risks is presented in chapter three. Chapter four analyzes the frequency and severity of highlighted risks and assesses their impact. Chapter five presents some stakeholder perceptions of risks and evaluates levels of vulnerability among various livelihood groups. The study concludes in chapter six with an assessment of priorities for risk management and a broad discussion of possible risk management measures that can help to strengthen the resiliency of agricultural supply chains and the livelihoods they support.